European survey of hepatitis B vaccination policies for healthcare workers: An updated overview. Issue 11 (4th March 2020) - De Schryver, Antoon; Lambaerts, Tom; Lammertyn, Nathalie; François, Guido; Bulterys, Simon; Godderis, Lode
Highlights: HBV Vaccination is mandatory for medical and nursing staff in 10 of 28 EU member countries. HBV vaccination schedule most often used is 0, 1, 6 months (16 member countries). Serotesting after vaccination is done in 16 member countries. Boosters were recommended in 12 countries. There is a large variation in the translation of EU legislation into practice in EU member countries. Abstract: Background: The risk of transmission of bloodborne pathogens, including hepatitis B virus (HBV) to healthcare workers (HCWs) is well known. In 2005 we performed a survey on HBV prevention in HCWs in the European Union (EU). An update of the 2005 survey deemed necessary as an EU Council Directive (2010/32/EU) on sharps injuries was to be implemented into national legislation by 11 May 2013 and more countries were starting universal HBV vaccination. Methods: We performed an electronic survey in 2016, among national representatives from the Occupational Medicine section of the European Union of Medical Specialists (UEMS), to find out how policies have been put into practice in the European Union countries (plus Norway and Switzerland). The data were updated in 2019. Results: Answers were received from 21 countries (among them 19 EU Member States), representing 78% of the population and 60% of HCWs in the EU-28. HBV vaccination was mandatory for medical and nursing staff in 10 countries; for other paramedical staff, medical and nursing students in 9 countries; for paramedical students in 8 countries; for cleaning staff in 7 countries; and for technical staff in 5 countries; it was recommended in all but one of other countries. Serotesting before vaccination was done in 7 countries. The vaccination schedule most often used was 0, 1, 6 months (18countries), monovalent HBV vaccine was used in 14 countries, and combined (HAV + HBV) vaccine in 11 countries. Serotesting after vaccination was done in 18 countries and boosters were recommended in 14 countries. A non-responder policy was present in 18 countries. HBV vaccination coverage (5 countries) was 70–95%. Sharps injuries were reported in 13 countries, nationwide in 7 of them; European-wide reporting was not mentioned by respondents. Discussion: These results show the variation in the implementation of EU legislation in the participating countries. More consultation between actors at EU level, including enhancing medical surveillance in occupational medicine could help to optimise policies in European countries in order to further reduce HBV transmission to HCWs.